Singapore : Detailed Assessment of Implementation-IOSCO Objectives and Principles of Securities Regulation. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2013)
This paper discusses the findings of the Detailed Assessment of Implementation on the International Organization of Securities Commissions (IOSCO) Objectives and Principles of Securities Regulation on Singapore. Overall compliance with IOSCO principles is generally high, although the assessors identified some vulnerabilities that need to be resolved. The Monetary Authority of Singapore's (MAS) enforcement philosophy as regards securities markets and the financial intermediaries active therein is cogent, with outcomes focused and well developed. The Securities and Futures Act (Cap. 289) provides an effective framework to enable the sharing of information and cooperation between MAS and foreign regulators on supervisory and enforcement matters.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet